2018
DOI: 10.1080/13632434.2018.1430688
|View full text |Cite
|
Sign up to set email alerts
|

The role of principals in creating inclusive school environments: insights from community national schools in Ireland

Abstract: This article seeks to provide an insight into the role of school principals dealing with newly multicultural and multi-faith student populations by drawing on a mixed-methods study on statefunded multi-denominational community national schools in Ireland. The study explores the extent to which school principals address the increasing social and cultural diversity in their schools by helping to establish inclusive and supportive school environments. The study identifies the main agents in shaping the school cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 33 publications
(28 reference statements)
1
14
0
Order By: Relevance
“…It is interesting to notice that no matter what organizational model a particular school district deploys, and no matter how conflicting the models are between the districts and even countries, they are almost always legitimized by policy-makers, school leaders and teachers as inclusion (Hiorth 2019;Vogel and Stock 2018;Bartlett, Mendenhall, and Ghaffar-Kucher 2017;Tajic and Bunar 2020). In other words, both 'refugee-only' schools (Mendenhall, Bartlett, and Ghaffar-Kucher 2017) and schools with direct immersion of NAMSs in mainstream classes (Grigt 2017;Faas, Smith, and Darmody 2018) are presented as inclusive education.…”
Section: Newly Arrived Migrant Students In International Researchmentioning
confidence: 99%
“…It is interesting to notice that no matter what organizational model a particular school district deploys, and no matter how conflicting the models are between the districts and even countries, they are almost always legitimized by policy-makers, school leaders and teachers as inclusion (Hiorth 2019;Vogel and Stock 2018;Bartlett, Mendenhall, and Ghaffar-Kucher 2017;Tajic and Bunar 2020). In other words, both 'refugee-only' schools (Mendenhall, Bartlett, and Ghaffar-Kucher 2017) and schools with direct immersion of NAMSs in mainstream classes (Grigt 2017;Faas, Smith, and Darmody 2018) are presented as inclusive education.…”
Section: Newly Arrived Migrant Students In International Researchmentioning
confidence: 99%
“…The study focused on better understanding the multi-denominational primary sector in Ireland across dimensions including school choice, student profile and school profile, with a focus on Educate Together Schools. In 2018, the ESRI published a number of papers with a focus on better understanding different characteristics of Community National Schools, including on the role of principals in creating inclusive school environments (Faas et al, 2018a), children's agency in multi-belief settings (Faas et al, 2018b), and variations in school ethos among schools within the same (multi-) denominational mission (Faas et al, 2019).…”
Section: Executive Summarymentioning
confidence: 99%
“…Research has also examined how senior school leaders create inclusive school environments in new systemic structures emerging that are deliberately designed to respond to this increasing pluralism and diversity in contemporary Irish society (Faas et al, 2018). Describing the principals as being at the vanguard of the change intended by these systemic structural reforms, Faas et al (2018) reported on the challenges and opportunities experienced by leadership in such contexts, most pronouncedly in the inclusive and equitable interpretation and enactment of religious education curriculum. Further research has begun to theorize leadership practices in multi-ethnic schools (Devine, 2013).…”
Section: Leading For Equality Inclusivity and Carementioning
confidence: 99%